Use of industrial boiler ash as partial replacement for Portland cement in mortars - L. S. Brandão, Fernanda (2022)
Civil construction has sought alternatives for cost reduction with the insertion of new products and techniques that guarantee better performance of buildings. In this context, the present work is based on the analysis of properties of mortars, produced with partial replacement of the Portland cement (CP) by ash from the burning of eucalyptus wood and grevílea in the boilers of a footwear industry. To perform this research, mortars with mix of 1:3 and 1:6 were produced, with partial substitutions of CP by the residual boiler ash (CRC) in the proportions of 0, 5, 10 and 15%. Tests of axial compressive strength, tensile strength by diametrical compression, absorption of water by immersion and by capillarity were performed. It was observed that the use of CRC resulted in improvements in the properties analyzed in mortars with increasing ash content, leading to significant increases in compressive strength and reduction of water absorption.